Mechanism and Therapeutic Targets of c-Jun-N-Terminal Kinases Activation in Nonalcoholic Fatty Liver Disease - Robert W. M. Min; Filbert W. M. Aung; Bryant Liu; Aliza Arya; Sanda Win (Biomedicines, 2022)
Non-alcoholic fatty liver (NAFL) is the most common chronic liver disease. Activation of mitogen-activated kinases (MAPK) cascade, which leads to c-Jun N-terminal kinase (JNK) activation occurs in the liver in response to the nutritional and metabolic stress. The aberrant activation of MAPKs, especially c-Jun-N-terminal kinases (JNKs), leads to unwanted genetic and epi-genetic modifications in addition to the metabolic stress adaptation in hepatocytes. A mechanism of sustained P-JNK activation was identified in acute and chronic liver diseases, suggesting an important role of aberrant JNK activation in NASH. Therefore, modulation of JNK activation, rather than targeting JNK protein levels, is a plausible therapeutic application for the treatment of chronic liver disease.